Temperature dependence of the deformation behavior and mechanical properties of a Fe–Mn–Al–C low-density steel for cryogenic application - Qi Zhang; Guanghui Chen; Haijiang Hu; Wanjie Zheng; Xiangliang Wan; Zhengliang Xue; Guang Xu (Journal of Materials Research and Technology)
The temperature dependence of the deformation behavior and mechanical properties of a Fe–20Mn–6Al-0.6C-0.15Si austenitic low-density steel was studied by tensile test and Charpy impact test at −196 °C, −77 °C and room temperature (RT), followed by microstructure analyses. The results indicate that the decreased tensile temperature, which is corresponding to reduced stacking fault energy (SFE), promotes the planar glide of dislocations. This led to larger fraction of low-angle grain boundaries (LAGBs) at lower tensile temperature. Consequently, both the tensile strength and elongation were improved as temperature decreased. At lower impact test temperature, the load and energy of crack initiation were larger, indicating a higher resistance to crack initiation. However, the transition from stable to unstable crack propagation occurred more rapidly at lower temperature, resulting in lower crack propagation energy and reduced resistance to crack propagation. This is because less region experienced planar glide. Due to the rapid unstable crack propagation, the Charpy absorbed energy at −196 °C was the lowest. The smaller fracture surface area, larger fibrous zone and more obvious ductile fracture characteristics in radial zone suggest that the toughness is better at higher temperature. Additionally, the presence of secondary cracks at RT delayed fracture, therefore benefitting toughness.